If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = 4 + 3y Solving 25 = 4 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 25 + -3y = 4 + 3y + -3y Combine like terms: 3y + -3y = 0 25 + -3y = 4 + 0 25 + -3y = 4 Add '-25' to each side of the equation. 25 + -25 + -3y = 4 + -25 Combine like terms: 25 + -25 = 0 0 + -3y = 4 + -25 -3y = 4 + -25 Combine like terms: 4 + -25 = -21 -3y = -21 Divide each side by '-3'. y = 7 Simplifying y = 7
| 8b-11+3b=121 | | 284-2x=43x+19 | | -2(y-4)=12-y | | 25x^2-49=0 | | c^2=25 | | 5xn-3=32 | | 5(y+2)+3y=50 | | 3t+8t+3t+3t= | | 11-9x=87-37x | | -2w+5=26+w | | 8x=64 | | -5(x+37)= | | 15x^3+44x^2+11x-6=0 | | 6(x-5)=5(x+5) | | -90-9x=9x+18 | | -2x^2+128=0 | | 4x^2=26x-30 | | 11x-(6x+6)=19 | | 2x+14=-41-9x | | 7b+5b= | | 2(y-12)+2y=-84 | | -20(-31)= | | -2[y-4]=12-y | | 5(3x-4)=2(5x+20) | | 3b=45 | | 100-4x=2x+22 | | 5+x=7 | | x+8x+9x= | | 2L*2-3=12 | | 4y-3(y+8)=12 | | -4x^2+16=0 | | 26=x-12 |